O luto infantil e a construção de significados familiares frente à morte de um ente querido - Hispagnol, Isabela Garcia Rosa (2011)
The present qualitative study aimed to investigate the family meaning-making of the grief and its relation with the child grief process. One case study was carried out with a family, whicj had a six year old child, bereaved due to the death of a loved one, four months before the study. The research data was generated by: genogram construction, semi-directed interviews and Film Script technique. The central family meanings found here was: unexpected death; the death does not make sense; the death could be prevented; the death could not be prevented; someone is responsible for the death; the deceased is responsible for the death; I was responsible for the death; God was responsible for the death; the deceased was strong; he doesn t want to die; he did not take care of himself; I can deal the suffering; I cannot deal with the suffering; i have to be strong; we have to move on; I cannot count on others; I don t feel safe; I can count on others; God helps me; He stopped suffering; He is better there; the deceased is going to be always with us; I occupy the deceased place; I don t know who I am anymore; Who i don t want to be; I feel calm; I am stronger than before. The meaning construction was related to: family dynamics, circumstances of death, relationship with the deceased, relationship with others (especially with the surviving parent) and self-perception. Among these factors, those related to the child grief were discussed